Impact of hematologic toxicities during concurrent chemoradiation for cervical cancer - Feiya Shi; Alison K. Yoder; Claire Mach; Shraddha Dalwadi; Matthew L Anderson; Tracilyn R Hall; Michelle S Ludwig (Korean Society of Obstetrics and Gynecology, 2022)
Objective To evaluate the prognostic significance of hematological toxicities during cervical cancer treatment. Methods Patients treated for cervical carcinoma with definitive chemoradiation were identified. Toxicities were assessed during weeks 1 to 6 of concurrent external beam radiation and chemotherapy. Outcomes were analyzed using Cox regression analysis. Results One hundred twenty-one patients with Federation of Gynecology and Obstetrics stage I-III disease were eligible for analysis. Median age at diagnosis was 45 years (interquartile range, 40-52) with median follow-up time of 34 months (95% confidence interval, 30.8-37.2). All patients experienced some grade of hematologic toxicity. The most common grade 3+ toxicities were low absolute lymphocyte count (n=115, 95%), low white blood cell count (n=21, 17%), and anemia (n=11, 9%). The most common grade 4 toxicity was lymphopenia, experienced by 36% of patients (n=44). Grade 4 lymphopenia was associated with reduced overall survival (hazard ratio [HR], 4.5; P=0.005), progression-free survival (HR, 3.4; P=0.001), and local control (HR, 4.1; P=0.047). Anemia grade 3, 4 was also associated with reduced overall survival (HR, 4.1; P=0.014). After controlling for disease and treatment variables, grade 4 lymphopenia remained significantly associated with reduced overall survival (HR, 9.85; P=0.007). The association with grade 4 lymphopenia only remained significant in women of Hispanic ethnicity. Conclusion Severe lymphopenia was associated with reduced overall survival and progression-free survival in Hispanic women undergoing definitive chemoradiation for cervical cancer, but not associated with outcomes in non-Hispanic women.